Analysis of the Application of the Virginia Solid Waste Management Hierarchy Concept on Urban Waste Management in Cirebon City, Indonesia - Juliarba, Muhammad; Kurniasari, Opy (Research and Social Study Institute, 2024)
Effective and sustainable waste management is a challenge faced by many cities worldwide, including Cirebon City. This study aims to analyze the effectiveness and sustainability of waste management strategies in Cirebon City using the Virginia Solid Waste Management Hierarchy Concept as the primary reference. The method consisted of field surveys, interviews with relevant stakeholders, and collection of secondary data regarding waste management in Cirebon City. Additionally, the Delphi method was employed to collect opinions and perspectives from a panel of experts and stakeholders regarding waste management strategies and programs. The analysis results of Delphi method reveal that short-term and medium-term programs will focus on socialization and study activities, then in the long-term program, strict regulations and incinerator construction will begin to be implemented. Based on the results of Simple Additive Weighting (SAW) analysis, which compared the implementation value of the Virginia Solid Waste Management Hierarchy Concept with that of the existing management concept, it is revealed that the implementation value of the Virginia Solid Waste Management Hierarchy Concept is greater, namely 2.15, thus demonstrating the potential for its application in waste management in Cirebon City.